Respuesta :
Answer:
[tex]f {}^{ - 1}(x) = \frac{x}{3} + 4[/tex]
Step-by-step explanation:
[tex]y = 3x - 12[/tex]
Flip the variables then solve for y
[tex]x = 3y - 12[/tex]
[tex] \frac{x}{3} = y - 4[/tex]
[tex] \frac{x}{3} + 4 = y[/tex]
[tex]f {}^{ - 1} (x) = \frac{x}{3} + 4[/tex]
y=3x-12 (Rewrite the equation)
x= 3y-12 (switch the place of x and y)
x+12/3 = 3y/3 (divide 3 by both sides)
1/3x +4=y
y= 1/3x+4
x= 3y-12 (switch the place of x and y)
x+12/3 = 3y/3 (divide 3 by both sides)
1/3x +4=y
y= 1/3x+4